Intravenous methadone in the management of acute postoperative pain in a chronic cancer pain patient: A case report and review of the literature - Khang Duy Ricky Le; Jean Hua (Clinical Case Reports, 2023)
Key Clinical Message The current landscape of literature highlights that there is insufficient well‐powered and robust evidence to support the integration of intravenous methadone into current guidelines and frameworks in supporting the pain management of cancer patient with complex pain syndromes. However, there is preliminary evidence, both from the literature as well as this case study that highlights intravenous methadone may be efficaciously and safety used for the management of postoperative pain in cancer patients with chronic pain undergoing operative management. Further research is required to fully elucidate key considerations of integrating this medication into clinical practice including consideration into dosing, opioid conversion, tolerance, and safety. Abstract Methadone is a broad‐spectrum analgesic with long duration of effect. Its multimodal mechanism of action, such as through effects on mu‐opioid receptor and presynaptic N‐methyl‐D‐aspartate receptors, has led to its current use in the management of opioid dependence in the community and in palliative care. These properties however make methadone appealing in the management of postoperative pain, particularly for patients with complex analgesic requirements. We report on an interesting case whereby intravenous methadone was effectively used for postoperative analgesia in a 56‐year‐old female with complex chronic pain secondary to a mucinous pelvic neoplasm of unclear primary who underwent palliative resection. Further, we review the literature surrounding usage of methadone in this setting to understand current challenges and barriers to implementation of methadone as an analgesia option for chronic pain patients following surgery. To do this, a case report and literature review was conducted in accordance to the CARE case report guidelines. The patient provided written consent for the de‐identification and use of their medical information and data for the generation and publication of this case report. Our case report and literature review demonstrate there remains significant heterogeneity, unfamiliarity, and scarce use of intravenous methadone in the perioperative and postoperative space in the management of patients with complex pain regimens such as chronic cancer pain patients. Despite this, our case report and literature review highlight as a broad analgesic, intravenous methadone warrants consideration following more rigorous research and development of safe use guidelines into its use for this purpose.